2018
DOI: 10.1634/theoncologist.2017-0577
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Results of Therapeutic Ratio by Intensity-Modulated Radiotherapy Versus Two-Dimensional Radiotherapy in Patients with Nasopharyngeal Carcinoma

Abstract: The ultimate therapeutic ratio of intensity-modulated radiotherapy versus two-dimensional radiotherapy in patients with nasopharyngeal carcinoma is unclear. In this retrospective study of 1,276 patients with nonmetastatic nasopharyngeal carcinoma with a follow-up of 115 months, intensity-modulated radiotherapy demonstrated an improved ultimate therapeutic ratio compared with two-dimensional radiotherapy, with significant improvement of local failure-free survival, failure-free survival, and overall survival an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 23 publications
0
46
0
1
Order By: Relevance
“…Over the years, radiotherapy technology has evolved from two-dimensional radiotherapy (2DRT) to intensity-modulated radiotherapy (IMRT) and this has resulted in longer survival and milder toxicity in NPC patients (4). Chen et al reported that NPC patients with IMRT had better failure-free survival and overall survival than patients with 2DRT, and the incidence of toxicity in the IMRT group, such as dry mouth, was lower than in the 2DRT group (5). Deutsch et al also reported that IMRT had reduced the risk of long-term sequelae, such as xerostomia in patients with head and neck carcinoma (6).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, radiotherapy technology has evolved from two-dimensional radiotherapy (2DRT) to intensity-modulated radiotherapy (IMRT) and this has resulted in longer survival and milder toxicity in NPC patients (4). Chen et al reported that NPC patients with IMRT had better failure-free survival and overall survival than patients with 2DRT, and the incidence of toxicity in the IMRT group, such as dry mouth, was lower than in the 2DRT group (5). Deutsch et al also reported that IMRT had reduced the risk of long-term sequelae, such as xerostomia in patients with head and neck carcinoma (6).…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned above, IMRT could lead to ideal local control. Large‐scale retrospective studies showed that advent of IMRT made the 10‐year LR rate of NPC decrease to only 3.5%‐5.0% . It is superior to conventional 2‐dimensional radiotherapy in precise dose delivery, which simultaneously realizes maximal tumor killing and protection of adjacent normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing application of intensity-modulated radiotherapy (IMRT), the incidence significantly decreased to 5% [3]. IMRT enables the delivery of the prescribed RT dose to the planning target volumes (PTV), and allows for the reduction the dose for organs at danger, such as the temporal lobe, brainstem, and optic chiasm [4]. The IMRT technology is able to create precision delivery of dosage to tumors by using beam collimation techniques (Multileaf Collimators) and feedback controlled intensity distribution through computation [5].…”
Section: Introductionmentioning
confidence: 99%